Impact of different beam directions on intensity-modulated radiation therapy dose delivered to functioning lung tissue identified using single-photon emission computed tomography - Tian, Qin; Zhang, Fucheng; Wang, Yanming; Qu, Weiqiang (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : To use different beam arrangements and numbers to plan intensity-modulated radiation therapy (IMRT) and investigate their effects on low and high radiation doses delivered to the functional lung, in order to reduce radiation-induced lung damage. Material and methods : Ten patients with stage I–III non-small cell lung carcinoma (NSCLC) underwent IMRT. Beam arrangements were selected on the basis of orientation and dose-volume histograms to create SPECT-guided IMRT plans that spared the functional lung and maintained target coverage. Four different plans, including CT-7, SPECT-7, SPECT-4, SPECT-5 with different beam arrangements, were used. The differences of conformity index (CI), heterogeneity index (HI) between the plans were analyzed, by using a paired t-test. Results: The seven-beam SPECT (SPECT-7) plan reduced the volume of the functional lung irradiated with at least 20 Gy (FV20) and 30 Gy (FV30) by 26.02% ±15.45% and 14.41% ±16.66%, respectively, as compared to the seven-beam computed tomography (CT-7) plan. The CI significantly differed between the SPECT-7 and SPECT-4 plans and between the SPECT-5 and SPECT-4 plans, but not between the SPECT-5 and SPECT-7 plans. The CIs in the SPECT-5 and SPECT-7 plans were better than that in the SPECT-4 plan. The heterogeneity index significantly differed among the three SPECT plans and was best in the SPECT-7 plan. Conclusions : The incorporation of SPECT images into IMRT planning for NSCLC greatly affected beam angles and number of beams. Fewer beams and modified beam angles achieved similar or better IMRT quality. The low-dose volumes were lower in SPECT-4.